Interaction of rabeprazole with phenytoin sodium: a prospective study - Kshirsagar, Pramod Mohanrao; Chandaliya, Kantilal C.; Baig, Mirza Shiraz (International Journal of Research in Medical Sciences, 2024)
Background: Phenytoin Sodium, a commonly prescribed anti-epileptic, with narrow therapeutic index, may interact with Rabeprazole, a commonly used Proton Pump Inhibitor (PPI), as both are metabolized by CYP2C19, potentially impacting bioavailability, therapeutic outcomes, and patient safety. Methods: A total of 52 epileptic patients, previously stabilized on phenytoin, have now been prescribed Tab Rabeprazole for a minimum of 30 days and were included in the study after meeting the other inclusion criteria. On day-0, a blood sample was collected from these patients, and plasma phenytoin level was determined using High-Performance Liquid Chromatography (HPLC). Additionally, clinical evaluations and assessments of other routine laboratory parameters were conducted. The Follow-up evaluations was done on day-15 and day-30, replicating the procedures employed on day-0, including both clinical, laboratory assessments and plasma phenytoin level measurement using HPLC. All data was recorded in the case report form, and statistical analysis was done. Results: The mean Phenytoin level exhibited a non-significant increase, rising from 15.49 μg/ml on day-0 to 15.57 μg/ml on day-15 and further to 15.75 μg/ml on day -0. Notably, there was no change in epilepsy outcomes concerning both seizure frequency and adverse effects. Additionally, there were no statistically significant changes observed in epilepsy control, SBP, DBP, and routine laboratory parameters, including haemoglobin, TLC, DLC, platelet count, serum albumin, serum globulin, serum bilirubin, SGOT, SGPT, serum urea, serum creatinine, and BSL (random). Conclusions: The co-administration of rabeprazole with Phenytoin resulted in a non-significant increase in Phenytoin levels, while maintaining stable control of epilepsy.